1975
DOI: 10.1002/bit.260171203
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methanol, formaldehyde, and formic acid on growth of Candida boidinii 11 Bh

Abstract: The dependence of the specific growth rate of Candida boidinii 11 Bh on methanol concentration follows Monod-type kinetics only in a narrow concentration range (0--0.8 v/v), with a saturation constant of about 19 mmol. With a further increase in methanol concentration of up to 3% v/v, the specific growth rate remains constant. Beyond this level, the growth rate gradually drops to zero, reaching the threshold value at 7.8% v/v. The specific growth rate is also strongly dependent on the size of the inoculum. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 16 publications
2
14
1
Order By: Relevance
“…The requirements and tolerance of methylotrophic yeast for methanol appears to be relatively constant between species. For example, Pilat and Prokop (1975) reported that C. boidinii growth followed Monod-type kinetics over a narrow range of methanol concentration (0%-0.8% v/v), and that the specific growth rate gradually became inhibited at methanol levels above 3% (v/ v).…”
Section: Resultsmentioning
confidence: 99%
“…The requirements and tolerance of methylotrophic yeast for methanol appears to be relatively constant between species. For example, Pilat and Prokop (1975) reported that C. boidinii growth followed Monod-type kinetics over a narrow range of methanol concentration (0%-0.8% v/v), and that the specific growth rate gradually became inhibited at methanol levels above 3% (v/ v).…”
Section: Resultsmentioning
confidence: 99%
“…This value is close to the assumption that in Candida boidinii the oxidation of formaldehyde via formate to CO2 is coupled to ATP production, and that the dual substrate specifity of alcohol oxidase results in a decreased cell yield. The cell yield of Candida boidinii depends on the methanol concentration; increasing the methanol con-centration in the culture medium results in a decreased cell yield and an increase in CO2 production [85,86]. It seems that the lower cell yields at higher methanol concentrations are due to uncoupling of methanol oxidation and ATP production [85].…”
Section: H a R A C T E R I Z A T I O N O F Microbial S Y S T E M Smentioning
confidence: 99%
“…The basis for this hypothesis was data published by Harrison et al (1972) concerning the effect of initial methanol concentration on the yield co- Until recently, insufficient data had been published for methanol-utilizing yeasts, to determine if a similar relationship exists, although yield depression by methanol in both Candida biodinii (Volfov~and Pil~t, 1974;Pil~t and Prokop, 1975) …”
Section: Yield Depression Observationsmentioning
confidence: 94%